2017
DOI: 10.1007/s00438-017-1294-4
|View full text |Cite
|
Sign up to set email alerts
|

The human RIT2 core promoter short tandem repeat predominant allele is species-specific in length: a selective advantage for human evolution?

Abstract: Evolutionary analyses of the critical core promoter interval support a selective advantage for expanding the length of certain short tandem repeats (STRs) in humans. We recently reported genome-wide data on human core promoter STRs that are "exceptionally long" (≥6-repeats). Near the top of the list, the neuron-specific gene, RIT2, contains one of the longest GA-STRs at 11-repeats. In the present study, we analyzed the evolutionary implications of this STR across species. We also studied this STR in a sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The Ras like without CAAX 2 gene (RIT2) is regulated by one of the longest STRs identified in a human gene core promoter, expansion of which may be of selective advantage in human-specific characteristics. In line with the above notion, the predominant allele of the RIT2 core promoter STR is human-specific in length [2].…”
Section: Ranian R Ehabilitation Journalmentioning
confidence: 60%
“…The Ras like without CAAX 2 gene (RIT2) is regulated by one of the longest STRs identified in a human gene core promoter, expansion of which may be of selective advantage in human-specific characteristics. In line with the above notion, the predominant allele of the RIT2 core promoter STR is human-specific in length [2].…”
Section: Ranian R Ehabilitation Journalmentioning
confidence: 60%
“…With respect to promoter dinucleotide polymorphisms in general, these are recognized to be correlated with gene expression (Bilgin Sonay et al 2015 ), being observed in numerous promoters (Sugiyama et al 2011 ; Ohadi et al 2012 ; Nikkhah et al 2015 ; Liu et al 2015 ; Emamalizadeh et al 2017 ), and forming potential “tuning knobs” of gene expression (Abe and Gemmell 2016 ; Sawaya et al 2012 , 2013 ; Vinces et al 2009 ). The reported effects of STR variation are gene-specific, resulting in either enhanced (e.g., Sugiyama et al 2011 ) or reduced (e.g., Liu et al 2015 ; Chen et al 2016 ) promoter activity, as a function of increasing dinucleotide repeat length.…”
Section: Discussionmentioning
confidence: 99%
“…CT-repeats (or GA-repeats in complement), also known as GAGA-elements, act as chromatin remodelling mediators by disrupting and displacing pre-assembled nucleosomes [5658]. Emamalizadeh and colleagues [59] suggested that the (GA) 11 repeat length in the promoter of RIT2 is crucial for obtaining the correct dosage of RIT2, important in regulating the neuronal function. A shorter allele (GA) 5 in homozygous state has been detected only in a proband with schizophrenia thus linking it to the disease state.…”
Section: Discussionmentioning
confidence: 99%